Sport injury prevention anatomy - Potach, David 1970-; Meira, Erik 1976-
"This book gives a detailed look into common sports injury conditions and exercises to prevent their occurrence. The text provides step-by-step exercise descriptions and full-color anatomical illustrations, highlighting the primary and secondary muscles. The book divides sports injuries by body segments-beginning with the head and neck down to the lower leg and feet. Sample programming templates, as well as how to incorporate the exercises into an existing training plan, are also included"